Does Visual Aesthetics of the Workplace Matter? Analyzing the Assessment of Visual Aesthetics as Antecedent of Affective Commitment and Job Crafting. (2019) - González-Suhr, Carolina; Salgado, Sergio; Elgueta, Herman; Alcover, Carlos-María
Abstract: In this work, two objectives were addressed. First, the visual aesthetics assessment of the workplace was explored for the first time as a potential antecedent of the proactive behaviors of job crafting. Second, the potential mediating role of the affective organizational commitment in this relationship was analyzed. To address these purposes, a field study was conducted with a sample of 428 workers. Following a set of hypotheses, the results of the measurement model, χ 2 ( df ) = 494.288 (215); CFI = .920; TLI = .906; RMSEA = .066, showed that the visual aesthetics assessment of the workplace was significantly correlated with three of the four dimensions of job crafting ( r = .19 with ISO-JR, r = .15 with IC-JD and; r = .17 with IST-JR; p < .001) and with affective organizational commitment ( r = .27, p < .001). In addition, through a structural equation model, χ 2 ( df ) = 494.895 (219); CFI = .921; TLI = .909; RMSEA = .065, positive and significant indirect effects were found from the visual aesthetic assessment of the workplace to the same three dimensions of job crafting, all through the affective organizational commitment: .17 with ISO-JR, .25 with IC-JD and, .23 with IST-JR; 95% CI [.097, .276], [.161, .361] and [.161, .361], respectively. The results obtained provide useful evidence for researchers and managers about the value of providing an aesthetically satisfactory workplace, which would enhance the affective commitment of employees and, consequently, positively affect the proactive behaviors of job crafting.